2011
DOI: 10.1007/s10450-011-9323-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel adsorbent hollow fibres for oxygen concentration

Abstract: The research examined the development of adsorbent hollow fibres as a low pressure drop structure for the production of oxygen-enriched air. The potential benefits of using a low pressure drop flexible adsorbent structure with molecular sieving properties over a bed packed with pellets include a low attrition resistance which could extend the life of the adsorbent structure. Highly macroporous, highly adsorbent loaded (up to 90 wt%) fibres were produced. By increasing adsorbent density, the separative performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Experimental and theoretical studies have shown that parallel passage adsorbent contactors, such as hollow fibers, are preferable to traditional packed beds for applications where pressure drop is important . Hollow fibers comprising polymers and inorganic porous materials have been prepared by a variety of spinning methods and are potential alternatives to the use of packed bed adsorbents. , Thin fiber walls allow rapid heat transfer, while the hollow fiber structure provides rapid mass transfer and minimizes pressure drop. , Hollow fibers may be spun in multiple layers thereby allowing materials with a wide range of properties to be developed. A hollow fiber adsorption system with rapid heating using a suitable electrically conducting material for regeneration and rapid cooling due to the low thermal mass has major advantages compared to existing packed bed technology.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies have shown that parallel passage adsorbent contactors, such as hollow fibers, are preferable to traditional packed beds for applications where pressure drop is important . Hollow fibers comprising polymers and inorganic porous materials have been prepared by a variety of spinning methods and are potential alternatives to the use of packed bed adsorbents. , Thin fiber walls allow rapid heat transfer, while the hollow fiber structure provides rapid mass transfer and minimizes pressure drop. , Hollow fibers may be spun in multiple layers thereby allowing materials with a wide range of properties to be developed. A hollow fiber adsorption system with rapid heating using a suitable electrically conducting material for regeneration and rapid cooling due to the low thermal mass has major advantages compared to existing packed bed technology.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical expressions for w c can be derived from the equation above as a function of the system's characteristic length. For rounded geometries, the corrected thickness has to be calculated from Equation (10), which equates the area of the solid around the channel, A S , to the area of the solid surrounding a hollow cylinder with the same free cross-section:…”
Section: Correlations For the Corrected Thicknessmentioning
confidence: 99%
“…In gas separation processes, structured adsorbents can achieve better performance in terms of pressure drop with high gas or liquid velocities and faster cycle times than packed bed adsorption columns 1–3,6 . Some structured adsorbent applications in gas separation processes are carbon capture, 7–9 air separation, 10,11 VOC removal, 12–14 and desiccant cooling 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Consequently, reforming processes with mediocre thermal efficiencies are only economical on a large scale. 25,26 With regards to nitrogen supply for ammonia synthesis, while hollow fibre-based membranes enable efficient air separation on all scales, 27 conventional air separation units (ASU) that provide nitrogen for many ammonia synthesis plants have also been found to benefit from economies of scale. 17,20 Therefore, the conventional ammonia manufacturing process as a whole is ideally suited for large-scale operation.…”
Section: Introductionmentioning
confidence: 99%